Analysis of Organizational Readiness towards Library 4.0: A Case Study at X Library - Qomariyah, Astutik Nur; Mursidah, Eva; Gonti, Yeni Anita; Wahyuni, Davi (Record and Library Journal, 2020)
Background of the study: The reality of the inevitability of the Industrial Revolution 4.0 era that must be faced by X University and will have an impact on the X Library towards Library 4.0 has become a serious concern at X University. Thus, it is important to conduct a research study on the readiness of the X Library in implementing Library 4.0.Purpose: The purpose of this study is to identify and analyze the readiness of the X library to implement Library 4.0 in the face of the Industrial Revolution 4.0 by referring to the TORC (Theory of Organizational Readiness for Change), in terms of five contextual factors- the policies and procedures, past experience, organizational resources (human resources and technological resources), organizational structure, and organizational culture.Method: The research method used this study is mixed methods, which combine quantitative and qualitative approaches.Findings: The results showed that the level of organizational readiness in implementing Library 4.0 is the mean value of 2,60. This showed that the X Library is not ready, and needs some of work to implement Library 4.0Conclusion: Based on the five contextual factors to measure organizational readiness toward Library 4.0, it showed that almost all of them are the level of not ready, but there is one factor that shows it is quite ready- the policies and procedures. The lack of organizational readiness because leadership is an important key related to contextual factors that affect the readiness of Library X towards Library 4.0.